Do Admissions Multiple Mini-Interview and Traditional Interview Scores Predict Subsequent Academic Performance? A Study of Five California Medical Schools. (March 2019) - Jerant, Anthony; Henderson, Mark C.; Griffin, Erin; Hall, Theodore R.; Kelly, Carolyn J.; Peterson, Ellena M.; Wofsy, David; Tancredi, Daniel J.; Sousa, Francis J.; Franks, Peter
Abstract : Purpose: To compare the predictive validities of medical school admissions multiple mini-interviews (MMIs) and traditional interviews (TIs). Method: This longitudinal observational study of 2011–2013 matriculants to five California public medical schools examined the associations of MMI scores (two schools) and TI scores (three schools) with subsequent academic performance. Regression models adjusted for sociodemographics and undergraduate academic metrics examined associations of standardized mean MMI and TI scores with United States Medical Licensing Examination Step 1 and Step 2 Clinical Knowledge (CK) scores and, for required clerkships, with mean National Board of Medical Examiners Clinical Science subject (shelf) exam score and number of honors grades. Results: Of the 1, 460 medical students, 746 (51.1%) interviewed at more than one study school; 579 (39.7%) completed at least one MMI and at least one TI. Neither interview type was associated with Step 1 scores. Higher MMI scores were associated with more clerkship honors grades (adjusted incidence rate ratio [AIRR] 1.28 more [95% CI 1.18, 1.39; P < .01] per SD increase) and higher shelf exam and Step 2 CK scores (adjusted mean 0.73 points higher [95% CI 0.28, 1.18; P < .01] and 1.25 points higher [95% CI 0.09, 2.41; P = .035], respectively, per SD increase). Higher TI scores were associated only with more honors grades (AIRR 1.11 more [95% CI 1.01, 1.20; P = .03] per SD increase). Conclusions: MMI scores were more strongly associated with subsequent academic performance measures than were TI scores. Abstract : Supplemental Digital Content is available in the text.